2022
DOI: 10.1186/s12955-022-02054-1
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder pain, shoulder disability, and depression as serial mediators between stress and health-related quality of life among middle-aged women

Abstract: Background This study analyzed the mediating effects of shoulder pain, disability, and depression on the relationship between stress and health-related quality of life among middle-aged women using a serial mediation model. Methods. Data on stress, health-related quality of life, shoulder pain, shoulder disability, and depression were collected from 565 women aged 35–64 years living in Seoul, South Korea, from May 13 to 23, 2021, using a self-reported, structured survey. SPSS PROCESS macro (Mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Moreover, age may be a key factor in regulating quality of life. Disability increases with age, although older patients have better mental health than younger patients [54].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, age may be a key factor in regulating quality of life. Disability increases with age, although older patients have better mental health than younger patients [54].…”
Section: Discussionmentioning
confidence: 99%
“…There is a straight connection between shoulder pain and decreased shoulder function and quality of life decreases and stress increases. 5 The annual economic impact of a patient unable to work secondary to shoulder pain is on average $14,356 US dollars. 6 A clinical algorithm to perform a better clinical evaluation of patients is recommended to be used, evaluation of possible trauma, discard referred pain, evaluate extra articular pathology, and evaluate intra articular pathology.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Furthermore, research has indicated that physical and psychological factors, including conditions such as shoulder pain and disability, depression, and sleep problems, can worsen fatigue. [9][10][11]14] Previous research demonstrates that when stress levels are high, shoulder pain and disability worsen, [15] and these issues with shoulder pain and disability negatively impact sleep quality. [16] Studies have also suggested a link between fatigue and sleep dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] In terms of the factors associated with fatigue, mechanisms such as overexertion, sleep disturbances, stress, depression, shoulder pain or disability, infections, endocrine disorders, and metabolic conditions have been suggested. [15,16,20,21] However, none of these factors alone can fully explain fatigue. Therefore, it is necessary to analyze the various factors influencing fatigue, considering their impact on physical fatigue and mental fatigue.…”
Section: Introductionmentioning
confidence: 99%